2009
DOI: 10.1182/blood-2009-05-222380
|View full text |Cite
|
Sign up to set email alerts
|

Altered fibrin clot structure/function in patients with idiopathic venous thromboembolism and in their relatives

Abstract: We tested the hypothesis that fibrin structure/function is unfavorably altered in patients after idiopathic venous thromboembolism (VTE) and their relatives. Ex vivo plasma fibrin clot permeability, turbidimetry, and efficiency of fibrinolysis were investigated in 100 patients with first-ever VTE, including 34 with pulmonary embolism (PE), 100 first-degree relatives, and 100 asymptomatic controls with no history of thrombotic events. Known thrombophilia, cancer, trauma, and surgery were exclusion criteria. VTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
261
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(286 citation statements)
references
References 33 publications
17
261
0
Order By: Relevance
“…Demographic and clinical data were recorded on the day of blood sampling. 5,6,8 Follow-up started at the time of discontinuation of anticoagulant therapy and was carried out on the 6-month basis (a visit at the center or telephone contact). We recorded the objectively documented recurrence of CVST.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and clinical data were recorded on the day of blood sampling. 5,6,8 Follow-up started at the time of discontinuation of anticoagulant therapy and was carried out on the 6-month basis (a visit at the center or telephone contact). We recorded the objectively documented recurrence of CVST.…”
Section: Methodsmentioning
confidence: 99%
“…1 The risk of recurrent CVST is 3% and remains higher in the first year after discontinuation of anticoagulant therapy, with no association with mild thrombophilias. 4 Unfavorable fibrin characteristics including faster formation of denser fibrin clots resistant to lysis represent a novel risk factor for both venous thromboembolism 5 and ischemic stroke. [6][7][8] We hypothesized that CVST is also associated with altered fibrin clot phenotype.…”
mentioning
confidence: 99%
“…[3][4][5][6] Previous studies have highlighted the importance of clot microstructure and how it affects the rate of clot lysis, where densely organised clots have been linked to thromboembolic disease. [7][8][9][10] This study investigates the in-vitro effect of dilution with saline on the organization and arrangement of clot microstructure and how this affects the mechanical properties of the developing clot. The aim is to determine whether quantifying the changes in clot microstructure provides an improved clinical biomarker of haemostasis and clot quality, particularly in the setting of surgery, trauma and critical illness where the administration of resuscitation fluids and the associated effect on coagulation and clot quality still poses a significant clinical issue.…”
Section: Introductionmentioning
confidence: 99%
“…Less compact fibrin structure associated with faster clot lysis seems to characterize patients who experienced PE, regardless of the presence of concomitant DVT. 61 It might be speculated that higher K s combined with shorter lysis time, found in patients with PE compared with DVT, contributes to clot fragmentation and the subsequent embolization. 61 Recently published computational model simulations describing interactions between main clot components under shear flow suggest that blood clots with higher clot shell permeability are more prone to embolization under increasing shear rate.…”
mentioning
confidence: 99%
“…61 It might be speculated that higher K s combined with shorter lysis time, found in patients with PE compared with DVT, contributes to clot fragmentation and the subsequent embolization. 61 Recently published computational model simulations describing interactions between main clot components under shear flow suggest that blood clots with higher clot shell permeability are more prone to embolization under increasing shear rate. 62 It has been reported that some environmental factors affect fibrin clot structure in patients with DVT.…”
mentioning
confidence: 99%